Development Model of China’s Regional Economic Cooperation Based on Network Analysis and Multimedia Data Visualization - Feng Du (Advances in Multimedia)
As for the problem of large amount and complex structure of network forum data, we analyze the means of data visualization and association analysis, explain the specific interpretation of association rules, explain the feelings and objectives of multimedia data visualization, and explain the corresponding technical application. This paper uses the relevant theories of new economic geography to analyze and compare China’s unique economic development. In particular, it studies the development and changes of the World Trade Organization. Through the results, it can be seen that, after China’s accession to the WTO, the industrial location coefficient shows a downward trend, and the change of economic differences is slow.